The use of paradigmatic research: The model of a perfect world according to Targum Qohelet - Lincoln, Lawrence (HTS teologiese studies, 2020)
The purpose of this study is to identify and explain a religious paradigm in Targum Qohelet (TgQoh). Targum Qohelet is dated to a period between 500 CE and 1101 CE. This study concludes that the most probable setting for this Targum was the beit midrash (the house of study). A paradigmatic research approach is used to identify the range of translation components to explain the translation method employed in TgQoh and the rationale behind it. This research approach reveals how the translator(s) used their interpretative ability to create a completely different thought-world when compared with the original Hebrew Text. Various subparadigms emerge as a network of connected religious beliefs to form a cogent systematic rabbinic theology of a perfect world order to replace the pessimism of the Hebrew base text. The Aramaic version reflects a complete solution to the existential problems raised by Biblical Qohelet. It seeks to provide humankind with guidelines for creating a ‘perfect world’ both on earth and in the afterlife. The use of a paradigmatic analysis based on the concept of a ‘perfect world’ provides an ideal model for analysing the translation strategy of TgQoh and understanding its method of rendering.Contribution: The application of paradigmatic methodology bridges the gap between the relatively secular nature of the Hebrew version of Qohelet (Ecclesiastes) and the overwhelmingly and inescapable theological forms of the Aramaic targum. The paradigms in the Aramaic translation identify how the targum applied rabbinic ideology to explain the meanings that lies behind the original Hebrew text of Qohelet. The paradigms, when taken together reveal how the cynical nature of Hebrew Qohelet was changed into a rabbinical guide for righteous living, here described as ‘perfect world’.